PENGARUH MINAT BELAJAR TERHADAP HASIL BELAJAR BAHASA SUNDA PADA SISWA DI SEKOLAH DASAR - Sandy Dermawan; Nurlinda Safitri; Dendy Saeful Zen (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research aims to determine the influence of interest in learning on the learning outcomes of class IV students in Sundanese language subjects at State Elementary School 06 Bojonggede. The type of research used in this research is quantitative research with a causal method approach. The population of this research was 106 students at SD Negeri 06 Bojonggede. Meanwhile, the sample for this research was 70 students in class IVA and IVB. Data collection techniques use observation, questionnaires and documentation. Observation and documentation are used to make observations and record the number of students. Questionnaires are used to reveal the influence of learning interest variables on student learning outcomes. The research results reveal that the variable interest in learning has a significant positive effect on student learning outcomes. This type of research is quantitative correlational research. Data collection techniques use questionnaires and documentation. Determining the sample in this research uses the total sample, namely making all members of the population as samples. Meanwhile, this research data analysis uses the product moment correlation formula. The results of this research show that (1) The interest in learning of class IV students at SD Negeri Bojonggede 06 is in the high category as many as 6 respondents (13%), in the medium category as many as 33 respondents (72%), and in the low category as many as 6 respondents (13%). It can be said that the interest in learning of class IV students at SD Negeri Bojonggede 06. (2) The results of learning Sundanese were in the high category as many as 7 respondents (14%), in the medium category as many as 34 respondents (73%), and in the low category as many as 8 respondents ( 6%). Thus, it can be said that the learning outcomes of class IV students at SDN Negeri Bojonggede 06 are moderate. (3) There is a significant influence between interest in learning and the science learning outcomes of class IV students at SD Negeri Bojonggede 06, namely the value obtained from the product moment correlation calculation of 0.817.